Analysis of association between panniculitis and tuberculosis infection in 33 cases - Xiaoxiao CHEN; Xin LI; Xiaojiao ZHAO; Xia YOU; Jian LONG; Ping HE; Jia YUAN; Zhaogui LIU; Shuang LI; Yi LEI; Xiyang DONG; Quan ZHOU; et al. (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To reveal the association between different types of panniculitis and tuberculosis infection. Methods The clinical data of 33 patients with panniculitis were collected from January 2019 to December 2021 and analyzed association of epidemiology, clinical features, and pathological features with tuberculosis infection, efficacy of anti-tuberculosis treatment, and adverse reactions in some patients, and follow-up after the treatment. Results ①Among the 33 patients with panniculitis, 24 cases were erythema nodosum and 9 cases were Bazin's disease. The male to female ratio was 1∶4.5. The average age was 46 years, and the average disease duration was 10 months. ②The lesions with pain, erythema, nodules and swelling were observed in 90.91% of the patients, including a case of Bazin's disease with ulcer (3.03%). Fever, cough and night sweats were found in 18.18% of patients. Two cases with Bazin's disease had papulonecrotic tuberculid, and two patients with erythema nodosum had systemic multi-joint pain. ③Twenty-two of 33 (66.67%) patients with panniculitis were associated with tuberculosis infection. There were 9 cases of Bazin's disease and 13 cases of erythema nodosum with mycobacterium tuberculosis latent infection (LTBI). The positive rate of tuberculosis infection was significantly higher in patients with erythema induratum than in patients with erythema nodosum (P=0.020).④The pathological manifestations included septal panniculitis (11 cases), lobular panniculitis (3 cases) and mixed panniculitis (19 cases). Epithelial-cell granulomas, multinucleated giant cells, and caseous necrosis were seen in 22 patients associated with tuberculosis infection. Perivascular and fat septal lymphocytic infiltration in the dermis were observed in 11 patients unrelated to tuberculosis infection, with no epithelioid granuloma or multinucleated giant cells. All 33 patients showed negative for acid-fast staining, PAS staining and direct immunofluorescence. ⑤Among the 22 cases related to tuberculosis infection, 15 cases received anti-tuberculosis treatment, resulting in a cure rate of 68.18%, while the cure rate was 14.29% in 7 cases who declined anti-tuberculosis. Eleven patients unrelated tuberculosis infection were cured following the treatments with immunomodulatory combination therapy. No serious adverse drug reactions were observed. Conclusions The positive rate of tuberculosis infection in patients with Bazin's disease was significantly higher than that in patients with erythema nodosum. In patients with tuberculosis infection-related panniculitis, the cure rate of anti-tuberculosis therapy was significantly higher than that of immunomodulatory combination therapy. For erythema nodosum with no evidence of tuberculosis infection, immunoregulatory therapy may be effective. The etiology of erythema nodosum may be related to tuberculosis infection.